Liver resection for breast cancer-related liver metastases: a case report - Eko Adhi Pangarsa; Erik Prabowo; Subiyakto; Wasisto Dwi Yudisaputro; Hermawan Istiadi; Jessica Novia Hadiyanto; Kevin Tandarto; Daniel Rizky; Budi Setiawan; Damai Santosa; Catharina Suharti (Journal of Medical Case Reports, 2024)
Abstract Introduction Breast cancer liver metastasis presents a significant challenge in clinical oncology, with limited treatment options and poor prognosis. This case series study explores the extended survival achieved in breast cancer patients with liver metastases through a combination of surgical and medical interventions. Case presentation We present three cases of Javanese female patients with breast cancer (51 years old, 42 years old, and 55 years old) with liver metastases who underwent hepatic resection followed by systemic therapy. The cases illustrate successful outcomes with disease-free survival ranging from 5 to 31 months post-surgery. Key prognostic factors associated with improved survival include prolonged interval between initial diagnosis and detection of liver metastasis, liver-limited disease, positive response to preoperative systemic therapy, and expression of estrogen and progesterone receptors in the metastatic lesions. Conclusion These findings underscore the potential efficacy of a multidisciplinary approach integrating local hepatectomy with systemic therapy in selected patients with breast cancer liver metastasis. Further research is warranted to identify optimal patient selection criteria and refine treatment strategies for improved outcomes.